Making and Remaking a Social Science: Croatian Sociology from Socialism to Post-Socialism - Cosovschi, Agustín (Serendipities. Journal for the Sociology and History of the Social Sciences, 2025)
In this paper, I give an account of the history of Croatian sociology under socialism and I explore how the discipline underwent the transition to post-socialism, attempting to shed light on some of the effects that the Yugoslav breakup had on its institutions and its practitioners. Drawing on written and oral sources, also relying on data on authorship in the main sociological journal of the country, I argue that in the early 1990s Croatian sociology underwent a process of “republicanization/nationalization” and became detached from developments in other former Yugoslav republics. I also show that the nationalist and conservative political turn in the country translated into the decline of certain institutions that the new authorities identified as representatives of the Communist era.